Some ectoparasites of veterinary importance on Dwarf sheep and goats under traditional system of management in the humid forest and derived savanna zones of Nigeria - Opasina, B.A.; Dipeolu, O.O.; Fagbemi, B.O. (1983)
Reports on prevalence of ectoparasitic infestations on Dwarf breeds of sheep and goat in the humid and derived savanna zones of southern Nigeria, with particular reference to the incidence of ticks, lice, fleas and mange mites on goats in the derived savanna zone, to the relative populations of Rhipicephalus, lice and fleas found on the animals in the two zones and to the incidence of sarcoptic mange among Dwarf goats of different age-groups and sex.